2016
DOI: 10.2217/nnm-2016-0252
|View full text |Cite|
|
Sign up to set email alerts
|

Pluronic-Attached Polyamidoamine Dendrimer Conjugates Overcome Drug Resistance in Breast Cancer

Abstract: With optimized PF68 modification, PAMAM-PF68 conjugates can significantly overcome multidrug resistance in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Dendrimers 17,18 are hyperbranched, monodispersed macromolecules that have shown significant potential in gene delivery, 19,20 drug delivery, 20-22 imaging, 23 and numerous other applications related to nanomedicine. 24 Dendrimers offer unique physicochemical features such as (1) highly defined monodisperse structure, (2) nanometer size range, (3) multivalency, and (4) easy tuneability.…”
Section: Introductionmentioning
confidence: 99%
“…Dendrimers 17,18 are hyperbranched, monodispersed macromolecules that have shown significant potential in gene delivery, 19,20 drug delivery, 20-22 imaging, 23 and numerous other applications related to nanomedicine. 24 Dendrimers offer unique physicochemical features such as (1) highly defined monodisperse structure, (2) nanometer size range, (3) multivalency, and (4) easy tuneability.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with PAMAM‐paclitaxel is significantly more potent than with paclitaxel in inhibiting the proliferation of esophageal, gastric, and pancreatic cancer cell lines. Besides, compared to paclitaxel, treatment with PAMAM‐paclitaxel induces higher expression of P53 and P21 pro‐apoptotic proteins in AGS gastric cancer cell lines . Maltose‐modified poly (propylene imine) glycodendrimers (PPI‐m OS) loaded with cytarabine increase the drug cytotoxicity and apoptosis in 1301 and HL‐60 leukemic cell lines.…”
Section: Novel Strategies Against Mdrmentioning
confidence: 99%
“…Besides, compared to paclitaxel, treatment with PAMAM-paclitaxel induces higher expression of P53 and P21 pro-apoptotic proteins in AGS gastric cancer cell lines. 59 Maltose-modified poly (propylene imine) glycodendrimers (PPI-m OS) loaded with cytarabine increase the drug cytotoxicity and apoptosis in 1301 and HL-60 leukemic cell lines. In addition, through a significant increase in the cellular uptake of cytarabine by tumor cells, it is suggested that this delivery system is a versatile candidate overcoming MDR in resistant acute lymphoblastic leukemia cells with lower expression of hENT1.…”
Section: Dendrimersmentioning
confidence: 99%
“…Dendrimers are most commonly derived from polyamidoamine, affording a hydrophilic delivery system. Although no clinical data are available, a pluronic‐attached polyamidoamine dendrimer conjugates for doxorubicin successfully overcame multidrug resistance in both in vitro and in vivo breast cancer models . Furthermore, a folate receptor‐targeted dendrimer loaded with a small interfering RNA and cis‐diamine platinum exhibited enhanced therapeutic efficacy in vitro for lung cancer .…”
Section: Emerging Therapeutic Drug‐delivery Strategies For Lrrmentioning
confidence: 99%
“…Although no clinical data are available, a pluronic-attached polyamidoamine dendrimer conjugates for doxorubicin successfully overcame multidrug resistance in both in vitro and in vivo breast cancer models. 120 Furthermore, a folate receptor-targeted dendrimer loaded with a small interfering RNA and cis-diamine platinum exhibited enhanced therapeutic efficacy in vitro for lung cancer. 121 Although dendrimers are typically formulated for intravenous delivery, they can also be made in aerosol formulations, providing potential for targeted lung delivery.…”
Section: Peritoneal Surface Malignanciesmentioning
confidence: 99%